IMPROVING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT THROUGH KWL AT EIGHT GRADE OF SMP NEGERI 8 RAMBAH - Julianum Dongoran; Rivi Antoni (English Study Program University of Pasir Pengaraian, 2018)
This Research was classroom action research (CAR) to overcome the existing problem on the field and explained whether the KWL strategy could improve the students’ reading comprehension in Narrative Text. This research was conducted at SMP Negeri 8 Rambah. There were two cycles consisted of four meetings: plan, action, obvservation and reflection. Researcher used four instruments in collecting data: test, observation checklist, field notes and interview. Analyzed by qualitatively and quantitatively. The finding showed an improvement in students’ reading comprehension of narrative text the average students’ score in basic test 42%, cycle 1 was 50,8% and cycle 2 was 72,51%.